Epidemiology of Sudden Infant Death Syndrome in Brazil: An integrative review (Research, Society and Development, 2024)
Introduction: Sudden Infant Death Syndrome (SIDS) is defined as the sudden, unexpected and unexplained death of an apparently healthy baby less than one year of age. It is the main cause of post-neonatal mortality in the first year in developed countries, however, in Brazil, the syndrome is underdiagnosed and poorly documented. Objective: To identify in the literature the socio-epidemiological, behavioral and environmental characteristics of SIDS in Brazil. Methodology: This is an integrative review collected through the PubMed, SciELO and LILACS databases. Results: 53 articles were identified, 15 of which comprised this review. Ten studies analyzed the number of probable SIDS cases, six were carried out in Rio Grande do Sul, two in Ribeirão-Preto (SP), one in Belo Horizonte (MG) and one in the Federal District. Five studies were also found that addressed the prevalence of risk factors associated with SIDS and mothers' knowledge about safe sleeping habits. No studies were found that investigated socio epidemiological data regarding the syndrome in the north and northeast regions. Conclusion: Brazilian studies reported the presence of risk factors similar to those described in the world literature, such as prone position, bed rest, male sex and maternal smoking. It is necessary to carry out more campaigns to raise awareness among the general and medical communities of the importance of preventive measures in reducing deaths. In parallel, implement research protocols to reduce the underdiagnosis of this syndrome.